Identification and characterization of two mannan-binding lectin associated proteins in lectin complement pathway of grass carp. (February 2020) - Chen, Dan-Dan; Yao, Yuan-Yuan; Zhang, Yong-An
Abstract: The lectin pathway of complement activation is an important component of the innate immune response, which must be tightly controlled to maintain immune homeostasis. However, its control mechanisms have not been investigated in detail in bony fish. In this study, we identified and characterized two novel, phylogenetically conserved mannan-binding lectin (MBL)-associated proteins (MAps) of grass carp ( Ctenopharyngodon idella ), CiMAp27 and CiMAp39, which were truncated, alternatively-spliced forms of grass carp MBL-associated serine proteases (MASPs), CiMASP1 and CiMASP2, respectively. Gene expression profiling showed that both CiMAp27 and CiMAp39 were upregulated by low doses of Aeromonas hydrophila, and inhibited by high doses, which lead to the inference that these genes acted as immune factors in antibacterial defense. Sequence analysis showed that CiMAp27 lack a catalytic domain but retains two domains (CUB1-EGF) involved in the association with MBL, while CiMAp39 retained four domains (CUB1-EGF-CUB2-CCP1). Not only the two CiMASPs but also the CiMAps were detected in grass carp serum. Furthermore, both recombinant CiMASPs (rCiMASPs) and recombinant rCiMAps (rCiMAps) interacted with recombinant MBL and the two CiMAps competed with CiMASPs for binding to MBL, and hence inhibited downstream C4 binding. These results indicated that CiMAps acted as competitive inhibitors in the lectin complement pathway of grass carp. Highlights: CiMAp27 and CiMAp39, alternatively-spliced forms of CiMASP1 and CiMASP2, respectively, have been identified in grass carp. CiMASPs and CiMAps present in grass carp serum were detected by Immunoblotting. rCiMASPs and rCiMAps bind individually to rMBL and binding of rCiMASPs to rCiMBL was competitively inhibited by rCiMAps. RCiMAps act as competitive inhibitors in the lectin complement pathway of grass carp.